Redomesticating Almond to Meet Emerging Food Safety Needs - Gradziel, Thomas M. (Frontiers in Plant Science, 2020)
Almond is a desirable and high-quality food source where the presence of nut allergens and a vulnerability to aflatoxin and salmonella contamination represent threats to consumer safety. In 2019, over 1 billion kg. of almonds, representing over 80% of the world total, were produced in California from a relatively few varieties with a very narrow genetic-base. To address emerging needs mandated by cultural and climate changes, new germplasm has been introduced combining peach as well as wild peach and wild almond species. Advanced breeding selections incorporating exotic germplasm into a genetic background compatible with commercial production in California have demonstrated sizable reductions in level of kernel immunoreactivity as well as opportunities for improved control of aflatoxin and salmonella. Breeding strategies employed include direct selection for reduced kernel immunoreactivity from an introgression enriched germplasm, the integration and pyramiding of resistance to multiple components of the aflatoxin disease-insect complex, and introduction of novel nut and tree traits to facilitate mechanized catch-frame field harvesting to avoid contamination with soil-borne pathogens such as salmonella and E. coli, as well as agrochemical residues.